A Year in the Life of the Supreme Court - Wermiel, Stephen; Savage, David G., 1950-; Mauro, Tony; Kindred, Kay L.; Epstein, Aaron; Denniston, Lyle W.; Coyle, Marcia; Carelli, Richard; Barrett, Paul (Paul M.) (Book collections on Project MUSE., 1995)
Despite its importance to the life of the nation and all its citizens, the Supreme Court remains a mystery to most Americans, its workings widely felt but rarely seen firsthand. In this book, journalists who cover the Court-acting as the eyes and ears of not just the American people, but the Constitution itself-give us a rare close look into its proceedings, the people behind them, and the complex, often fascinating ways in which justice is ultimately served. Their narratives form an intimate account of a year in the life of the Supreme Court. The cases heard by the Supreme Court are, first an.